2013
DOI: 10.1371/journal.pone.0071717
|View full text |Cite
|
Sign up to set email alerts
|

Reactive-Oxygen-Species-Mediated P. aeruginosa Killing Is Functional in Human Cystic Fibrosis Macrophages

Abstract: Pseudomonas aeruginosa is the most common pathogen for chronic lung infection in cystic fibrosis (CF) patients. About 80% of adult CF patients have chronic P. aeruginosa infection, which accounts for much of the morbidity and most of the mortality. Both bacterial genetic adaptations and defective innate immune responses contribute to the bacteria persistence. It is well accepted that CF transmembrane conductance regulator (CFTR) dysfunction impairs the airways-epithelium-mediated lung defence; however, other i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 30 publications
0
35
0
1
Order By: Relevance
“…It is unclear if CF macrophages have basal deficits in oxidative killing since some studies have suggested functional ROS responses to pathogens such as P. aeruginosa (36), while others have demonstrated deficient ROS production (37). Importantly, a comprehensive assessment of human CF macrophage oxidase assembly has not been performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear if CF macrophages have basal deficits in oxidative killing since some studies have suggested functional ROS responses to pathogens such as P. aeruginosa (36), while others have demonstrated deficient ROS production (37). Importantly, a comprehensive assessment of human CF macrophage oxidase assembly has not been performed.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we examined the oxidative burst in response to another common CF pathogen, P. aeruginosa , which has been previously shown to not affect the respiratory burst in CF macrophages (36). There was no difference in ROS production in response to P. aeruginosa between CF and non-CF MDMs (Figures 8E, F), confirming previous findings.…”
Section: Resultsmentioning
confidence: 99%
“…In aerobes, oxidative stress is inevitable and, perhaps fortunately, cannot be completely prevented. Some free radicals escape detoxification and have essential functions in organisms, for example, the killing of invading bacteria by leukocytes and macrophages . Clearly, quenching all radicals with direct scavengers or enzymatic antioxidants would be detrimental.…”
Section: Melatonin Reduces Oxidative Stress: the Machinery And The Mementioning
confidence: 99%
“…We have previously shown that murine cftr −/− AMs are not defective in ROS production but are defective in microbicidal function (3), strongly suggesting that other microbicidal enzymatic effectors contributed by lysosomal fusion and activated in the acidic environment of the phagosome play a significant role in bacterial killing. Although both human and murine CF lung macrophages seem to be intrinsically defective in bacterial killing, there is disagreement in the literature as to whether CFTR dysfunction impairs the contribution of ROS production to P. aeruginosa killing (44,45) and may well be a function of species and tissue source.…”
Section: Direct Measurement Of (R)-roscovitine Induced Exocytotic Insmentioning
confidence: 99%